Origin and annals of "The Old south," First Presbyterian church and parish, in Newburyport, Mass., 1746-1896 - Hovey, Horace Carter (Damrell & Upham, 1896)
Introduction--Historical survey, by H. C. Hovey.--Reminiscences, by A. G. Vermilye.--Anniversary proceedings.--Appendix: The Albert Plumer memorial clock, and sundry bequests.--Historical aftermath, by H. C. Hovey.--General index.